CO2 and electrical stunning differentially affect energy metabolism in pigs - Manuela Peukert; Sebastian Zimmermann; Björn Egert; Dagmar Adeline Brüggemann (Scientific Reports)
Abstract The use of CO₂ or electrical stunning to render pigs unconscious and insensible before exsanguination is a common practice. Although both methods are widely implemented, they differ fundamentally in their underlying mechanisms, and studies have produced conflicting results regarding their influence on meat quality. In the case of CO₂ stunning, impaired pulmonary gas exchange causes a rapid onset of systemic hypoxia, accompanied by hypercapnia, which in turn lowers blood pH and triggers additional physiological stress responses. Electrical stunning, by contrast, induces a generalized epileptic seizure by depolarizing neuronal cell membranes, markedly increasing oxygen consumption in both the brain and peripheral muscles. Coupled with apnea-induced cessation of respiration, this leads to rapid systemic hypoxia and associated metabolic disturbances. With this study, we aim to generate comprehensive metabolic data as a foundation for deeper understanding of the animal’s physiological responses depending on the stunning method used. We identified differences in metabolite pathways associated with the stunning method and evaluated potential influence on early post mortem processes relevant to meat quality development. After CO2 stunning, there was a marked increase in purine degradation into inosine (p < 0.0001) and hypoxanthine (p < 0.0001), along with increased levels of C4 intermediates (succinate, fumarate and malate, all p < 0.0001) in the tricarboxylic acid (TCA) cycle. In contrast, electrical stunning showed a higher rate of glycolysis, as indicated by reduced levels of C6 sugars (e.g. glucose p < 0.0001), and elevated levels of TCA cycle entry metabolites such as citrate (p = 0.0053) and aconitate (p = 0.0009). Our findings suggest that purinergic signaling acts as a rapid emergency response mechanism during gas stunning, reflected by pronounced purine catabolism. The distinct metabolite patterns likely result from different physiological stress responses, such as CO2-induced acidosis and variable oxygen availability. In addition, differences in cellular redox balance (NAD⁺/NADH) between stunning methods may further modulate glycolytic flux and TCA cycle activity. These divergent metabolic states at the time of death may, in turn, influence subsequent post mortem biochemical processes and ultimately influence meat quality development.